Head-to-head comparison of four COVID-19 vaccines on platelet activation, coagulation and inflammation. The TREASURE study. Issue 223 (March 2023) - Brambilla, Marta; Canzano, Paola; Valle, Patrizia Della; Becchetti, Alessia; Conti, Maria; Alberti, Mariangela; Galotta, Arianna; Biondi, Maria Luisa; Lonati, Paola Adele; Veglia, Fabrizio; Bonomi, Alice; Cosentino, Nicola; et al.
Abstract: Introduction: Studies exploring alterations in blood coagulation and platelet activation induced by COVID-19 vaccines are not concordant. We aimed to assess the impact of four COVID-19 vaccines on platelet activation, coagulation, and inflammation considering also the immunization dose and the history of SARS-CoV-2 infection. Methods: TREASURE study enrolled 368 consecutive subjects (161 receiving viral vector vaccines -ChAdOx1-S/Vaxzevria or Janssen- and 207 receiving mRNA vaccines -Comirnaty/Pfizer-BioNTech or Spikevax/Moderna). Blood was collected the day before and 8 ± 2 days after the vaccination. Platelet activation markers (P-selectin, aGPIIbIIIa and Tissue Factor expression; number of platelet-monocyte and -granulocyte aggregates) and microvesicle release were analyzed by flow cytometry. Platelet thrombin generation (TG) capacity was measured using the Calibrated Automated Thrombogram. Plasma coagulation and inflammation markers and immune response were evaluated by ELISA. Results: Vaccination did not induce platelet activation and microvesicle release. IL-6 and CRP levels (+30%), D-dimer, fibrinogen and F1 +2 (+13%, +3.7%, +4.3%, respectively) but not TAT levels significantly increased upon immunization with all four vaccines, with no difference among them and between first and second dose. An overall minor post-vaccination reduction of aPC, TM and TFPI, all possibly related to endothelial function, was observed. No anti-PF4 seroconversion was observed. Conclusion: This study showed that the four COVID-19 vaccines administered to a large population sample induce a transient inflammatory response, with no onset of platelet activation. The minor changes in clotting activation and endothelial function might be potentially involved at a population level in explaining the very rare venous thromboembolic complications of COVID-19 vaccination.